Audit Delay Ditinjau dari Ukuran KAP, Solvabilitas, Audit Tenure, dan Kompleksitas Operasi - Widiasari, Farida Nur Soleh; Samrotun, Yuli Chomsatu; Suhendro, Suhendro (Jurnal Riset Akuntansi, 2020)
The study was conducted to investigate the effect of KAP size, solvency, audit tenure, and complexity of operations on audit delay. The data used are secondary data derived from the financial statements of mining sector manufacturing companies listed on the Indonesia Stock Exchange in 2015 - 2018. The sample selection is done by purposive sampling, so that the total sample can be obtained as 57 samples. The analysis technique used is multiple linear regression processed with the SPSS 22 program. The results of the study simultaneously show that the size of the KAP, solvency, audit tenure, and complexity of operations affect the audit delay. While the research results partially state that the solvency and complexity of operations have an influence on audit delay, while the KAP size and audit tenure have no effect on audit delay. From the results of the study, is expected to assist auditors in identifying factor - factor that affect audit delay in optimizing performance and as a material consideration for investors in making investment decisions. Keywords: AudittDelay, KAP Size, Solvency, AudittTenure, Complexity of Operations